Implementasi Model Problem Based Learning dalam Menggali Kemampuan Berpikir Kritis dan Kolaborasi Peserta Didik di Mi Plus Al-Makmun Gemarang Madiun - Toiyibbatun Naafia; Marita Lailia Rahman; Sri Susanti Tjahja Dini (PT. Hasba Edukasi Mandiri, 2025)
This study analyzes the implementation of the Problem Based Learning (PBL) model in developing critical thinking and collaboration skills of fourth-grade students at MI Plus Al-Makmun Gemarang Madiun. The background of the study stems from the low level of active student involvement in conventional learning, which is still dominated by lecture methods. PBL was chosen because it provides a real-world problem-based learning experience that encourages thinking activities and social interaction. The study used a descriptive qualitative method with observation, interview, and documentation techniques. The focus of the study was directed at the implementation of PBL syntax, including problem orientation, information exploration, group discussions, presentation of results, and reflection. The results showed that the implementation of PBL was able to improve students' critical thinking skills, as seen from their ability to identify problems, analyze data, put forward arguments, and determine solutions independently. In addition, collaboration skills developed through role allocation, open discussions, and mutual assistance activities in groups. The learning process became more meaningful, interactive, and suited to the characteristics of students. Overall, PBL has proven effective for science learning in Madrasah Ibtidaiyah because it not only strengthens cognitive aspects but also develops 21st-century skills, especially critical thinking, communication, and cooperation.